Keynote Speakers - Grauman, Kristen; Kraut, Robert (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Biographical details and talk summaries for the keynote talks presented at the AAAI Conference on Human Computation and Crowdsourcing.